STANDAR ANALISA BELANJA KABUPATEN GRESIK - Mardiana, Lilik; Sukamto, Sukamto (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2014)
This study aims to determine how to set standards expenditure analysis (SAB) in allocating budgets to the respective work units within the organizational structure of the Government of Gresik. Results of this research are used to improve local budgeting mechanism through Standards Development Expenditure Analysis (SAB) is accurate and relevant to further integrate with the application system budget. Object of research is all activities performed on every SKPD in Gresik. While the activities used are activities related to the development of employees on the basis that these activities most relevant to measure the effectiveness of the use of the budget. The data used is data of the budget for development activities consisting of: a) personnel expenditures, which consists of: Shopping and Spending Non PNS PNS b) Expenditure Goods and Services, which consists of: Shopping Consumables, Shopping Materials Materials, Printing and Copying Shopping, Eating and Drinking Shopping, Travel Agency Shopping, Shopping Other. Preparation of Standard Expenditure Analysis using three main approaches, namely: the approach of Activity Based Costing (ABC), the approach Ordinary Least Square (simple regression) and approach to the discussion method (Focused Group Discussion). Standards Based Analysis Expenditure on education activities in Gresik showed that essentially all of the budget used for development activities of personnel or human resources is reasonable. Yet for Education and Leadership Training activity level II, III and IV using too large budget expenditure exceeds the maximum limit, resulting in inefficiencies or wasteful activities budget.